2018
DOI: 10.1371/journal.pone.0195869
|View full text |Cite
|
Sign up to set email alerts
|

Codon usage bias reveals genomic adaptations to environmental conditions in an acidophilic consortium

Abstract: The analysis of codon usage bias has been widely used to characterize different communities of microorganisms. In this context, the aim of this work was to study the codon usage bias in a natural consortium of five acidophilic bacteria used for biomining. The codon usage bias of the consortium was contrasted with genes from an alternative collection of acidophilic reference strains and metagenome samples. Results indicate that acidophilic bacteria preferentially have low codon usage bias, consistent with both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…In our current study on ATP6 and ATP8 genes among different species of fishes, birds, and mammals, we observed that the compositional properties and the shape of codon usage differed among these organisms. This is also related with the metabolic rate of an organism . The metabolic rate significantly varied among these organisms and also within each group since habitats were not the same .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our current study on ATP6 and ATP8 genes among different species of fishes, birds, and mammals, we observed that the compositional properties and the shape of codon usage differed among these organisms. This is also related with the metabolic rate of an organism . The metabolic rate significantly varied among these organisms and also within each group since habitats were not the same .…”
Section: Discussionmentioning
confidence: 99%
“…This is also related with the metabolic rate of an organism. 63,64 The metabolic rate significantly varied among these organisms and also within each group since habitats were not the same. 61 Among mammals, most of the species are terrestrial while some are aquatic.…”
Section: Discussionmentioning
confidence: 99%
“…Fast growing organisms with more abundant tRNA molecules tend to have high CUB for highly expressed genes (Rocha, 2004). Apart from playing a key role in evolution and adaptation biology (Hart, Cortés, Latorre, & Martinez, 2018;Roller, Lucić, Nagy, Perica, & Vlahoviček, 2013;Sharp & Matassi, 1994;Sharp, Emery, & Zeng, 2010), CUB has a prime role in improving the expression level of exogenous genes by the process of codon optimization (Mauro & Chappell, 2014). CUB is species-specific, with many potential environmental and intracellular dynamics affecting the CUB phenomenon (Grantham, Gautier, Gouy, Jacobzone, & Mercier, 1981;Plotkin, Robins, & Levine, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in diverse microbes supports the hypothesis that codon optimization can be used to identify associations between codon usage (either globally or in specific genes) and ecology [12,[39][40][41][42][43]. For example, an analysis of metagenomes collected from mine biofilms shows an enrichment of optimal codons in bacterial and archaeal genes associated with inorganic ion transport [39].…”
Section: Introductionmentioning
confidence: 83%